Diplomatic Immunity : The Glasgow School of Art MFA in NY. - Ainsley, Sam; Calcutt, John; Hunter College/Times Square Gallery, New York (Glasgow : The Glasgow School of Art, 2001)
Alleck, Nirveda ; Auderson, Jon ; Dee, Jason ; Doherty, Maurice ; Goh, Tamares ; Goto, Komachi ; Ikonen, Ilona ; Jameson, Patrick ; Katara, Elina ; Luckey, Clive ; et al.
Times Square Galery, Hunter College, New York, 10/04/2001 - 11/10/2001
kunstcatalogus